Fluorescent nanoparticles using hyaluronic acid-histidine-based manganese dioxide for hydrogen peroxide imaging in inflammatory macrophages - Hong, Ji Yeon; Park, Ji Sun; Park, Kyeongsoon (Macromolecular research, 2025)
The presence of excessive hydrogen peroxide (H 2 O 2 ) in the body plays a key role in inflammatory diseases. Among the various methods available, fluorescent nanoparticles have been used to detect H 2 O 2 in living cells. Herein, the design of CD44-targetable fluorescent nanoparticles is presented for intracellular H 2 O 2 imaging in inflammatory macrophages. Accordingly, CD44-targetable hyaluronic acid-histidine (HA–His) conjugates were sequentially reacted with permanganate and fluorescein (FL) to synthesize HA–His/MnO 2 /FL nanoparticles. These prepared HA–His/MnO 2 /FL nanoparticles exhibited good dispersibility in water and 10% fetal bovine serum solution. Owing to their rapid responsiveness to H 2 O 2 , the HA–His/MnO 2 /FL nanoparticles showed a good linear relationship with H 2 O 2 concentration (0–100 μM). Moreover, the CD44-targetable HA–His/MnO 2 /FL nanoparticles were readily internalized in lipopolysaccharide-induced inflammatory macrophages, allowing successful imaging of intracellular H 2 O 2 in inflammatory macrophages. Graphical Abstract The HA-His/MnO 2 /FL nanoparticles with H 2 O 2 responsiveness were readily internalized into activated macrophages, allowing successful intracellular H 2 O 2 imaging in inflammatory macrophages